PENGARUH IKLAN MEDIA SOSIAL, WORD OF MOUTH, DAN PERSEPSI KUALITAS TERHADAP KEPUTUSAN PEMBELIAN: Studi Pada Konsumen Dapoer Ami Tenjolayar - Neny Kusumadewi; Pipih Sopiyan (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
The more advanced and growing Indonesian society, which has transformed into a modern society and has high busy activities, tends to look for consumer food tastes online through social media. This study aims to determine the effect of social media advertising, word of mouth and perceived quality on purchasing decisions partially on consumers of Dapoer Ami Tenjolayar.The method used in this research is descriptive and verification method. The population in this study were consumers at Dapoer Ami Tenjolayar with a sample of 100 people using the incidental sampling method. The technique of collecting data is by using a questionnaire.Based on the results of this study, it shows that social media advertising, word of mouth and perceived quality have a positive and significant effect on purchasing decisions partially on Dapoer Ami Tenjolayar consumers.